2011
DOI: 10.1093/ejo/cjr042
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a hybrid genetic algorithm and artificial neural network system for predicting the sizes of unerupted canines and premolars

Abstract: The aim of this study was to develop a novel hybrid genetic algorithm and artificial neural network (GA-ANN) system for predicting the sizes of unerupted canines and premolars during the mixed dentition period. This study was performed on 106 untreated subjects (52 girls, 54 boys, aged 13-15 years). Data were obtained from dental cast measurements. A hybrid GA-ANN algorithm was developed to find the best reference teeth and the most accurate mapping function. Based on a regression analysis, the strongest corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
0
16
0
4
Order By: Relevance
“…Tik keliuose tyrimuose statistiškai reikšmingas skirtumas nebuvo nustatytas taikant Moyers 75 proc. proporcingumo lenteles [9,7]. Camilo Aquino Melgaco statistiškai reikšmingo skirtumo nenustatė tarp apskaičiuoto ir išmatuoto iltinių dantų ir kaplių MDP naudojant Bernabe Flores-Mir metodą moterims [7].…”
Section: Rezultatų Aptarimas (Diskusija)unclassified
See 3 more Smart Citations
“…Tik keliuose tyrimuose statistiškai reikšmingas skirtumas nebuvo nustatytas taikant Moyers 75 proc. proporcingumo lenteles [9,7]. Camilo Aquino Melgaco statistiškai reikšmingo skirtumo nenustatė tarp apskaičiuoto ir išmatuoto iltinių dantų ir kaplių MDP naudojant Bernabe Flores-Mir metodą moterims [7].…”
Section: Rezultatų Aptarimas (Diskusija)unclassified
“…Analizuojant tyrimo rezultatus pastebėta, kad tiriami metodai padidina iltinių dantų ir kaplių plotį. Ši metodų savybė buvo nustatyta ir kitų tyrimų metu [5,9,10,11,16,17]. Priešingi rezultatai gauti tik keliuose tyrimuose [4].…”
Section: Rezultatų Aptarimas (Diskusija)unclassified
See 2 more Smart Citations
“…Shankarapillai et al, showed that NN trained by Levenberg-Marquardet (LM) algorithm can be used effectively to diagnose the risk of periodontal diseases (11). Moghimi et al, conducted a study entitled "designing and using a combination of genetic algorithm and ANN to anticipate the size of hidden canines and premolar size", and found that the proposed method was an efficient tool to anticipate the size of hidden canines and premolar with high accuracy in comparison with regression analysis (12). According to the mentioned studies, it can be said that the unique capability of ANNs to differentiate, categorize, and diagnose diseases can be efficient and useful (13).…”
Section: Introductionmentioning
confidence: 99%